2010
DOI: 10.1097/acm.0b013e3181eb60f6
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Residency Program Designed to Develop Leaders to Improve the Health of Children

Abstract: Physician-leaders are needed to address the widening gap in health disparities in an increasingly complex health care system. To be effective leaders, physicians need specific training; yet despite its importance, leadership training is rarely addressed during graduate medical education. As a result, most physician leadership training occurs after residency training. To address this gap in medical education, in 2004 the authors developed the Pediatric Leadership for the Underserved (PLUS) program at the Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 24 publications
0
63
0
Order By: Relevance
“…127,128 Another training program reported positive results in training residents 129 and attributed the program's success to a longitudinal and skill-based structure that supported the residents in their leadership paths to advocate for children's health. Another small study showed that the Thomas-Kilmann Conflict Mode Instrument predicted Accreditation Council for Graduate Medical Education (ACGME) evaluations of residents, 129 suggesting the relevance of EI evaluation to ACGME competencies.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
See 1 more Smart Citation
“…127,128 Another training program reported positive results in training residents 129 and attributed the program's success to a longitudinal and skill-based structure that supported the residents in their leadership paths to advocate for children's health. Another small study showed that the Thomas-Kilmann Conflict Mode Instrument predicted Accreditation Council for Graduate Medical Education (ACGME) evaluations of residents, 129 suggesting the relevance of EI evaluation to ACGME competencies.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…In this way, the paucity of studies examining the impact of EI in medical leadership mirrors the lack of rigorous studies of the impact of leadership development in medicine in general. 83 On the basis of this review of available literature, perhaps the best available evidence supporting the role of EI as an essential competency for medical trainees and for senior physicians is the experience of programs that have used EI in their leadership development programs over extended periods of time, for example, the advocacy-focused program for residents at the University of California, San Francisco, which reported career and performance benefits from their intervention 128 ; the Cleveland Clinic's program, which has generated innovative business plans that helped improve care delivery 101 ; and the Mayo Clinic's programs, which have provided specialized support to program participants and helped them use their new skills and insights in a productive way within their institutions. 88 Although even these results are incomplete, the favorable experience of these and other programs seems to fuel growing enthusiasm for EI training in health care and justifies further study.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…Our suggestions would be to divide the topics into subjects suitable for junior medical residents and for residents who are more advanced in their specialist training program. In the literature, of the 32 training programs described, 21 used a subjective evaluation of which 21 [14,15,17,19,20,22,27-40] were positive and one was neutral [13]. Based on our own evaluation and the evaluations in the literature we also suggest that medical management training should be mandatory since we feel that all doctors should have a basic knowledge of these subjects and residents seem to have a need for it.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same search strategy as for the earlier literature review [8]. We found nine new articles describing a management program designed for medical residents [12-20]. In combination with our previous literature review a total of 32 articles described management training programs which focused on medical residents.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 An internal medicine program implemented a yearlong ambulatory block that provided flexible time for residents to pursue additional research or elective experiences within that year. 8 In addition, focused training throughout residency was used to prepare hospitalists 9 ; there is a longitudinal curriculum in pediatrics that encompasses the entire training period, 10 and Vinci et al 11 developed a 3-month research experience for senior pediatrics residents interested in an academic career. However, none of these innovations use resident learning goals to create a truly resident-specific individualized program that emphasizes self-directed learning.…”
Section: Introductionmentioning
confidence: 99%